1999
DOI: 10.1095/biolreprod60.2.305
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic Acid Sequence of Feline Preprorelaxin and Its Localization within the Feline Placenta1

Abstract: The cat placenta is known to secrete large amounts of relaxin. We employed uteroplacental tissue at approximately Day 35 of gestation to determine the nucleic acid sequence of feline preprorelaxin using reverse transcription- and rapid amplification of cDNA ends-polymerase chain reaction. Feline preprorelaxin cDNA was found to consist of 540 base pairs encoding a protein of 180 amino acids (aa). We identified a signal peptide of 25 aa, a B domain of 33 aa, a C domain of 98 aa, and an A domain of 24 aa. The put… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
(56 reference statements)
3
13
0
Order By: Relevance
“…We found relaxin signals not only in the same cellstrophoblast cells of the placental labyrinth -as described previously by Klonisch et al (1999a) but also in trophoblast cells of villous tips, extravillous trophoblast cells of placental junctional zone, giant cells, blood vessel cells, and cells that could not be further specified.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…We found relaxin signals not only in the same cellstrophoblast cells of the placental labyrinth -as described previously by Klonisch et al (1999a) but also in trophoblast cells of villous tips, extravillous trophoblast cells of placental junctional zone, giant cells, blood vessel cells, and cells that could not be further specified.…”
Section: Discussionsupporting
confidence: 82%
“…The origin of these placental cells was verified by immunoreactions against vimentin, which expresses specificity toward fetal mesenchyme cells, maternal endothelial cells, giant cells, and other maternal cells (as described here and by Walter & Schonkypl (2006)) and against E-cadherin, which detects epithelial cell. Klonisch et al (1999a) confirmed their immunostaining by in situ hybridization experiments, indicating that the source of relaxin was within the placenta. In some other species, the localization of relaxin was also analyzed in placental tissue.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations